INFLUENCE OF DIMENSIONAL DEVIATIONS OF MECHANICAL ELEMENTS IN THE KINEMATIC STRUCTURE OF SCARA INDUSTRIAL ROBOTS ON POSITIONING PRECISION AND TRAJECTORY ACCURACY - ANDREI LUNCANU; GHEORGHE STAN (Journal of Engineering Studies and Research)
The purpose of this article is to present the research on the influence of the dimensional deviations of the mechanical elements in the kinematic structures of the SCARA industrial robots regarding the positioning precision and trajectory error. In this article the direct kinematics method is used to calculate the positioning of the end-effector and generate the trajectory simulation with and without dimensional deviations.